الرعاية الأبوية وعلاقتها بتقدير الطفل لذاته في مرحلة الطفولة المتأخرة - الشماس عيسى; حمدي لميس ابراهيم (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يهدف البحث لتقصي العلاقة بين الرعاية الأبوية كما يدركها الأبناء وتقدير الطفل لذاته في مرحلة الطفولة المتأخرة بعمر (10) سنوات بمدارس مدينة اللاذقية، ولتحقيق أهداف البحث قامت الباحثة بتصميم أداتي الدراسة وهما (استبانة) لقياس الرعاية الأبوية كما يراها الأبناء، و(استبانة) أخرى تُقيس تقدير الطفل لذاته. تم تطبيق الأداتين على عينة مختارة عشوائياً مؤلفة من (137) طفل وانتهى البحث إلى النتائج الآتية : 1 - وجود علاقة دالة إحصائياً بين أساليب الرعاية الأبوية للأب وتقدير الذات الكلي للطفل في مرحلة الطفولة المتأخرة . 2 – وجود علاقة بين استخدام الأب لأسلوب الرعاية الايجابي وتقدير الذات الكلي للطفل وكان دالاً عند مستوى دلالة 0,01 . 3 – عدم وجود علاقة بين استخدام الأب لأسلوب الرعاية السلبي وتقدير الذات الكلي للطفل. 4 - عدم وجود فروق في مستوى تقدير الذات(الكلي) بين الأطفال تبعاً لمتغير الجنس. This research aims to investigate the correlation between the parent caring as the children realize it, and their self –esteem at the late childhood at ten years old in schools of Lattakia. To achieve the aims of this study, the researcher designed two tools: a questionnaire that measures the parental care as the children realize it and a questionnaire that measures the children’s self-esteem. The two tools were applied on a sample randomly selected, which consisted of (137) children. The results were as the following: 1- There is a statistically significant correlation between the methods of the parental care of the father and the child’s entire self-esteem at the late childhood. 2- There is a correlation between the positive method of the father concerning the parental care and the child’s entire self-esteem at the late childhood. It was significant at the indication level ( 0.01) . 3- There is no correlation between the negative method of the parental care of the father the child’s entire self-esteem. 4- There are no differences between children at the level of the entire self–esteem according to the gender variable .